Analysis of Attachment with Parents of Students with Problems - Indri Amanda; Afdal Afdal (Jurnal Neo Konseling, 2021)
Problematic students are students who show symptoms of behavior carried out by students in general. Problematic students can be built by the attachment between students and students. This research aims to describe attachment with parents to students in terms of trust, communication, and isolation aspects. This research uses quantitative methods with descriptive research type. The subjects of this study were students with problems in SMA Negeri 4 Padang, who were in 68 students. The data were obtained from a questionnaire using a Likert scale model. The results showed (1) attachment with parents to problem students was in the low category with a presentation of 66,18%, (2) attachment with parents to students based on the aspect of trust was in the high category with a presentation of 50%, (3) attachment of communication with parents to students, based on the aspect is in the low category with a presentation of 63,24%, (4) attachment with parents to students based on the aspect of alienation is in the high category with a presentation of 61,76 %. The implication of the research results can be used as one of the newest in providing BK services, especially those related to attachment with parents.